The Correlation between Human Posture and Musculoskeletal Disorder of Upper Extremities among Computer Workers at Indonesian State Owned Enterprises in Surabaya - Lupita Ghilang Laraz; Linda Dewanti; Andriati Andriati; Sulistiawati Sulistiawati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: Computer becomes a highly used and essential tool in daily life. This also applies to occupational level. However, there are risk factors in using the computer within daily life while working, one of them is the posture while working in front of computer. Due to the risk factors, computer workers develop complaint in upper extremities, but they tend to ignore it. The complaint silently decreases their life quality, efficiency, and productivity. This study aimed to find the correlation between human posture and musculoskeletal disorder (MSD). Methods: This was an observational analytic study, using total sampling technique. The subjects were the computer workers in Indonesian State Owned Enterprises in Surabaya. They were given NMQ for mapping the distribution of complaint. Observational sheets were provided to assess the human posture using NERPA Assessment Worksheet. Spearman’s rank method was used to observe the correlation between human posture and MSD. Result: 112 chosen subjects were involved. Human posture showed large correlation with MSD. This was calculated using alpha value 0.05 for the significance. Conclusion: There is a correlation between human posture and MSD among computer workers at Indonesian State Owned Enterprises in Surabaya.